Pregnancy-Related Low Back Pain and The Quality of Life among Pregnant Women : A Narrative Literature Review - Fatmarizka, Tiara; Ramadanty, Raudhatus Shofy; Khasanah, Dini Afriani (Journal of Public Health for Tropical and Coastal Region, 2021)
Introduction: Around 50-70% of pregnant women have reported pregnancy-related back pain during the second and third trimesters of pregnancy. Physical and physiological aspects during pregnancy might affect the quality of life (QoL) of pregnant women, and the problems due to the alteration can be seen in how they run their daily activities. The effect of LBP in pregnancy on the QoL among pregnant women must be known to avoid the pain that affects pregnant women’s activities and well-being. The aim of this study is to review the relationship between low back pain and the QoL during pregnancy.Methods: Using the search terms via PubMed and Google Scholar, seven cross-sectional studies have met the inclusion criteria and included for further analysis. The appraisal tool for Cross-Sectional Studies (AXIS) is used to assess the quality of the included studies including the risk of bias.Results: The findings show that LBP in pregnancy affects the level of quality of life such as sleep quality and sexual activity, limits the activities and productivities, and even make physical disability among pregnant women. The 75-90% was of the range score obtained from the AXIS critical appraisal.Conclusions: This review mentioned those pregnant women with PRBP had decreased QoL during and after childbirth, so the awareness of health professionals needs to be improved.